Supporting healthcare in rural communities in Thailand: An exploratory qualitative study to understand the role and current mental health practices of village health volunteers. - Chonmanan Khanthavudh; Annmarie Grealish; Vasiliki Tzouvara; Mary Leamy (PLoS ONE)
Introduction Village health volunteers (VHVs) are the backbone of primary healthcare in many low-and-middle-income countries, including Thailand, where healthcare professionals are scarce. Previous studies looking at their role have been broader and lacked a specific mental health focus. In 2019, Thailand introduced a policy endorsing a recovery orientation in mental health care, however, the potential for VHVs to implement the approach remains underexplored. This study aims to: [1] describe VHVs' mental health practices, [2] explore stakeholders' perspectives on these practices, and [3] understand stakeholders' views on their potential to deliver recovery-oriented community care. Method This exploratory qualitative study involved nineteen semi-structured interviews conducted between August 2023 and March 2024 in a rural subdistrict of Northern Thailand. Participants included ten VHVs, four nurses, four caregivers, and one individual with mental health conditions. Purposeful and snowball sampling techniques were used. Reflexive thematic analysis was used to analyse interview data. Official documents related to VHVs' job descriptions, training, and recruitment policies were also examined to understand the scope of the role. Results The analysis identified three main themes: [1] Mental health practices and roles perceptions, highlighting variability among VHVs; [2] Organisational constraints on mental health practice in the community, demonstrating limited policy support and training for VHVs; and [3] Factors influencing the implementation of recovery-oriented approaches by VHVs, including barriers such as stigma and workload, and enabling factors such as specialist training and professional support. Conclusions This study reveals that VHVs in Thai rural communities prioritise physical health due to policy adopting a biomedical approach and limited training on providing mental health care. A range of culturally adapted approaches are needed to expand and enhance the contribution that VHVs can make to improving the quality of life of individuals experiencing mental health conditions in rural communities in Thailand.